Analisis Efektivitas Sistem Informasi Akuntansi Penggajian Karyawan pada Perusahaan Penyedia Jasa Tenaga Kerja - Ekawati, Neneng; August Goenawan, Yohanes (JOURNAL INTELEKTUAL, 2022)
Introduction/Main Objectives: To find out and analyze the effectiveness of the payroll accounting information system that has been used by labor supply companies. Background Problems: The payroll system at the company does not have internal supervisors within the company. Novelty: The salary calculation system at the company can run well and has a positive impact, namely the performance of employees in the company is guaranteed and employee welfare. Research Methods: Using the slovin formula method, a sample of 88 respondents was obtained and the analytical technique used was the SPSS analysis tool. Finding/Results: Position level and length of service variables have a positive and significant effect on employee payroll, attendance and education level variables have no effect on employee payroll. Conclusion: That together the variables of attendance, education level, position level, and length of service simultaneously have a positive and significant effect on employee payroll.